Analysis of power quality and economic worthiness of electric motorcycle charging in a residential electrical system - Pathomthat Chiradeja; Atthapol Ngaopitakkul (My University, 2023)
Abstract In the urban society of Thailand, most people use motorcycles for travelling because they can meet the manoeuvrability of travelling in short distances and save energy compared to using a car. Many people are switching to electric motorcycles (EMCs), which install EMC chargers in their residential buildings. EMC chargers are power electronic devices that may produce electrical and electromagnetic interference; therefore, it is critical to evaluate the potential influence of an EMC charger on a household electrical system and other electrical equipment before installing one. Therefore, this study examined the effects of an EMC charger on residential electrical systems with and without a photovoltaic system connection as well as on individual load types in terms of power quality. The investigation revealed that EMC charging has a direct impact on the grid system's reactive power, power factor, and current harmonics. However, when the electrical load in the system has sufficient power, it is possible to reduce the reactive power and current harmonics of the grid. The cost of electricity when an EMC is connected to a residential electrical system was also analysed to determine the metre type and charging interval suitable for Thailand.
Keywords: Installation; Electrical equipment; Electromagnetic Compatibility; Electric Vehicles and Infrastructure